2012
DOI: 10.1158/1940-6207.capr-12-0091
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Risk for Premenopausal and Postmenopausal Breast Cancer

Abstract: Obesity has been consistently associated with an increased risk of postmenopausal breast cancer in population-based studies. Conversely, obesity in such studies has been inversely associated with premenopausal breast cancer risk. In a report of data from two large chemoprevention trials, both of which enrolled women at a high risk of breast cancer, obesity was associated with only a modest, nonsignificantly increased risk of postmenopausal breast cancer and a surprising statistically significant 70% increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 52 publications
1
60
1
1
Order By: Relevance
“…The relationship between overweight and increased breast cancer risk was consistently observed in postmenopausal women (4,5), whereas the association between body weight and premenopausal breast cancer risk is less clear (6)(7)(8). Several lines of evidence also suggest that increased body weight is associated with a worse prognosis: a shorter survival has been observed in obese women with early breast cancer (9)(10)(11)(12) and in those gaining weight after breast cancer diagnosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between overweight and increased breast cancer risk was consistently observed in postmenopausal women (4,5), whereas the association between body weight and premenopausal breast cancer risk is less clear (6)(7)(8). Several lines of evidence also suggest that increased body weight is associated with a worse prognosis: a shorter survival has been observed in obese women with early breast cancer (9)(10)(11)(12) and in those gaining weight after breast cancer diagnosis (13).…”
Section: Introductionmentioning
confidence: 99%
“…Production of estrogens after menopause, mostly takes place in the peripheral adipose tissues, catalyzed by cytochrome P450 dependent enzyme; aromatase enzyme, that converts androgen precursors into estrogens. CYP19 is the gene encoding aromatase and it is thought to be induced in postmenopausal women and not in premenopausal females [16,131]. Therefore, the greater risk of hormone receptor positive breast cancer in a post menopause period of overweight/obese women has been referred, in particular, to elevated estrogen production in adipose tissue by aromatase enzyme as a consequence of hyper adiposity [132].…”
Section: Sex Steroidsmentioning
confidence: 99%
“…It has been demonstrated that elevated circulating levels of free estrogen, as well as estrone and androgens, are associated with breast cancer [31]. Therefore, Increased BMI has been associated with increased the risk of postmenopausal breast cancer not premenopausal breast cancer [16,34,131].…”
Section: Sex Steroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, breast tissues of obese women (Morris et al 2011) as well as mammary glands of genetically modified and dietinduced obese mice (Subbaramaiah et al 2011) were shown to display subclinical inflammation characterized by increased P450 aromatase activity and enhanced NF-kB activity. As inflammation is a hallmark of cancer, the correlation of obesity with 'local' mammary adipocyte dysfunction may provide a rational basis for the increased risk and poor prognosis of breast cancer associated with obesity (Anderson & Neuhouser 2012).…”
Section: Introductionmentioning
confidence: 99%